2011
DOI: 10.1142/s0219749911008192
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian Geometric Discord

Abstract: We extend the geometric measure of quantum discord, introduced and computed for two-qubit states in 1 , to quantify non-classical correlations in composite Gaussian states of continuous variable systems. We lay the formalism for the evaluation of a Gaussian geometric discord in two-mode Gaussian states, and present explicit formulas for the class of two-mode squeezed thermal states. In such a case, under physical constraints of bounded mean energy, geometric discord is shown to admit upper and lower bounds for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 35 publications
1
63
0
Order By: Relevance
“…(7) with the restriction that the measurement of A is a general single-mode Gaussian POVM (Adesso and Datta, 2010;. These measurements are all executable using linear optics and homodyne detection (Giedke and Cirac, 2002).…”
Section: H Continuous-variable Discordmentioning
confidence: 99%
“…(7) with the restriction that the measurement of A is a general single-mode Gaussian POVM (Adesso and Datta, 2010;. These measurements are all executable using linear optics and homodyne detection (Giedke and Cirac, 2002).…”
Section: H Continuous-variable Discordmentioning
confidence: 99%
“…We also have investigated the CV geometric discord [19], comparing the Gaussian and non-Gaussian cases. We have shown that the behavior of geometric discord is completely different from that of quantum discord.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly D G = 0 iff D = 0, since both measures vanish on the set of classically correlated states. In particular, it has been be proven that D G can be seen a measure of the discrepancy between a state before and after a local measurement on subsystem B [34]: Analogous to the case of Gaussian discord, a Gaussian version of the geometric discord can be defined by restricting to Gaussian measurements [19]. Again, it can be analytically computed for two-mode Gaussian states.…”
Section: Geometric Discordmentioning
confidence: 99%
See 1 more Smart Citation
“…When applied to two-mode Gaussian states in Refs. [27,28], the definition (1.2) was modified by allowing general local measurements (POVMs).…”
Section: Introductionmentioning
confidence: 99%